Innovative teaching strategies in nursing and related health professions - Bradshaw, Martha J.; Hultquist, Beth L. (Jones & Bartlett Learning, 2017)
Innovative Teaching Strategies in Nursing and Related Health Professions, Seventh Edition details a wealth of teaching strategies, focusing on incorporating technology into the classroom, including the use of Web 2.0 technologies like blogs and podcasts. Chapters on blended learning and study abroad programs are featured, enabling students to gain a more diverse and increased global perspective. Highlighting innovative teaching techniques for various learning environments and real-world illustrations of the strategies in use, this text goes beyond theory to offer practical application principles that educators can count on. The Seventh Edition includes two new chapters - Teaching through Storytelling and Giving and Receiving Evaluation Feedback-- Provided by publisher.